Customers' trust in e-commerce: in collective culture setting - Meskaran, Fatemeh (IEEE, 2012)
A major problem facing the full deployment of business-to-consumer (B2C) electronic commerce (e-commerce) is the development of trust on the side of the consumer, particularly in developing countries. Differing characteristics of local environments and their cultures have created a significant level of variation in the acceptance and trust to e-commerce and e-transactions. Exploring influencing factors on trust may be considered an important issue for different cultures. This paper attempts to investigate factors related to trust in developing countries, which are typically collective culture by nature. Various models that proved to be appropriate in understanding trust for B2C are under consideration. The review process revealed that reputation, security, privacy and type of payment are probable antecedents of trust in collective culture setting. In addition, recommendation from friends and family is noted to be an influencing factor for reputation of online vendors in collective cultures.